Domestic Violence Alleged in California Child Maltreatment Reports During the COVID-19 Pandemic - Rebbe, Rebecca (Journal of family violence, 2022)
During the COVID-19 pandemic, reports to child abuse and neglect hotlines have dropped significantly across the United States. Yet, during this same period, calls to domestic violence hotlines have increased. The purpose of this study was to examine if there have been measurable changes in domestic violence-related reports to child abuse and neglect hotlines. Using administrative child protection records from California, we plotted counts and proportions of child maltreatment reports with and without domestic violence allegations before and through the onset of school closures associated with the COVID-19 pandemic. We used an interrupted time series analysis to evaluate whether or not there was a change in domestic violence allegations in child protection reports corresponding to the COVID-19 pandemic. We document that during the first two quarters of 2020 there was a 14.3% drop in the overall number of child protection reports. Despite a decline in maltreatment reporting overall, there was a 25% increase in the proportion of reports with allegations of domestic violence. Our findings suggest both the count and composition of reports to child protection agencies were affected by the COVID-19 pandemic. The current analyses also showcase the seasonality of CPS reports generally, and reports with DV allegations, specifically.